Pengaruh Faktor-Faktor Organisasi Tempat Duduk Terhadap Kualitas Pembelajaran di Sekolah Dasar - Mahmudah, Ashfa Nurul; Maharani, Ajeng Putri; Ramadhani, Moza Prameswari; Jabalrohmah, Nisa; Mustikaati, Wina (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Seating organization is one of the factors that determine the success of students in learning to achieve learning objectives.  This research aims to find out what factors influence seating organization on the quality of learning in elementary schools. The method used is qualitative research with the type of literature review. All data is taken from literature in the form of journals and books. The results of the research, after the search, can be seen in general to show that when the seating management determined by the teacher is appropriate, then the learning outcomes of students can run smoothly, and if on the contrary then learning will certainly not run smoothly.  In addition, student learning motivation will also increase, students will be more enthusiastic and enthusiastic in participating in learning because the teacher's view can focus on all students.